A Coherent Strategy for Data Security through Data Governance. - Trope, R.L.
The role of boards of directors now extends to ensuring that a company's data is actively managed in an increasingly technology-intense environment. In this article, the authors show how this requires greater attention to legislative requirements, greater due diligence in transactions and business alliances, and coherent information management strategies.